Exposure‐Response and Population Pharmacokinetic Analyses of a Novel Subcutaneous Formulation of Daratumumab Administered to Multiple Myeloma Patients. (3rd November 2020) - Luo, Man (Melody); Usmani, Saad Z.; Mateos, Maria‐Victoria; Nahi, Hareth; Chari, Ajai; San‐Miguel, Jesus; Touzeau, Cyrille; Suzuki, Kenshi; Kaiser, Martin; Carson, Robin; Heuck, Christoph; Qi, Ming; et al.
Abstract: We report the population pharmacokinetic (PK) and exposure‐response analyses of a novel subcutaneous formulation of daratumumab (DARA) using data from 3 DARA subcutaneous monotherapy studies (PAVO Part 2, MMY1008, COLUMBA) and 1 combination therapy study (PLEIADES). Results were based on 5159 PK samples from 742 patients (DARA 1800 mg subcutaneously, n = 487 [monotherapy, n = 288; combination therapy, n = 199]; DARA 16 mg/kg intravenously, n = 255 [all monotherapy, in COLUMBA]; age, 33‐92 years; weight, 28.6‐147.6 kg). Subcutaneous and intravenous DARA monotherapies were administered once every week for cycles 1‐2, once every 2 weeks for cycles 3‐6, and once every 4 weeks thereafter (1 cycle is 28 days). The subcutaneous DARA combination therapy was administered with the adaptation of corresponding standard‐of‐care regimens. PK samples were collected between cycle 1 and cycle 12. Among monotherapy studies, throughout the treatment period, subcutaneous DARA provided similar/slightly higher trough concentrations (Ctrough ) versus intravenous DARA, with lower maximum concentrations and smaller peak‐to‐trough fluctuations. The PK profile was consistent between subcutaneous DARA monotherapy and combination therapies. The exposure‐response relationship between daratumumab PK and efficacy or safety end points was similar for subcutaneous and intravenous DARA. Although the ≤65‐kg subgroup reported a higher incidence of neutropenia, no relationship was found between the incidence of neutropenia and exposure, which was attributed, in part, to the preexisting imbalance in neutropenia between subcutaneous DARA (45.5%) and intravenous DARA (19%) in patients ≤50 kg. A flat relationship was observed between body weight and any grade and at least grade 3 infections. The results support the DARA 1800‐mg subcutaneous flat dose as an alternative to the approved intravenous DARA 16 mg/kg.